2014
DOI: 10.1095/biolreprod.113.113977
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Stimulates the mTOR Signaling Pathway and Protein Synthesis in Porcine Trophectoderm Cells1

Abstract: Insufficient placental growth is a major factor contributing to intrauterine growth retardation in mammals. There is growing evidence that putrescine produced from arginine (Arg) and proline via ornithine decarboxylase is a key regulator of angiogenesis, embryogenesis, as well as placental and fetal growth. However, the underlying mechanisms are largely unknown. The present study tested the hypothesis that putrescine stimulates protein synthesis by activating the mechanistic target of rapamycin (mTOR) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 60 publications
3
51
0
1
Order By: Relevance
“…The results imply that the suppression of myoblast protein synthesis and muscle development induced by glucocorticoids is energy dependent, and that nutrition supplementation could relieve the stress response. These findings in chickens agree with a result in mammals (Kong et al, 2014), which revealed that AA administration promoted cell proliferation and protein synthesis by stimulating the mTOR-signaling pathway.…”
Section: Mtor Inhibition May Be Involved In Dexamethasonesuppressed Psupporting
confidence: 91%
See 1 more Smart Citation
“…The results imply that the suppression of myoblast protein synthesis and muscle development induced by glucocorticoids is energy dependent, and that nutrition supplementation could relieve the stress response. These findings in chickens agree with a result in mammals (Kong et al, 2014), which revealed that AA administration promoted cell proliferation and protein synthesis by stimulating the mTOR-signaling pathway.…”
Section: Mtor Inhibition May Be Involved In Dexamethasonesuppressed Psupporting
confidence: 91%
“…Leucine can stimulate the phosphorylation of S6K1 and eukaryotic initiation factor 4E binding protein1 (4EBP1) (Kimball et al, 1999;Kong et al, 2014), and increase tissue protein synthesis (Li et al, 2011;Yin et al, 2010). Shimizu et al (2011) reported that glucocorticoids inhibit mTOR activity via a distinct mechanism involving branched-chain amino acid transaminase 2 (BCAT2) gene activation.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to increased protein synthesis and whole-body growth [99]. Likewise, arginine or its metabolite putrescine activates mTOR to promote protein synthesis in placental cells and their proliferation [100]. In addition, dietary glutamine enhances intestinal integrity, cell survival, and villus height through the activation of mTOR cell signaling, while attenuating weaning-induced reduction in the abundances of occludin, claudin-1, zonula occluden (ZO)-2, and ZO-3 proteins [101].…”
Section: Fetal and Neonatal Programming Of Growth Development And Fementioning
confidence: 99%
“…et al, 2014a). Putrescine, which is a product of arginine catabolism in maternal tissues , can also stimulate protein synthesis in porcine placental cells (Kong et al, 2014). Of note, dietary supplementation of 0.8% L-arginine between Day 0 and Day 25 of gestation reduced litter size, uterine weight, total number of fetuses, number of corpora lutea and total fetal weights significantly at Day 25 .…”
Section: L-argininementioning
confidence: 99%